Dietary patterns and breast cancer risk in women participating in the Black Women’s Health Study(1)(2)(3)(4) - Agurs-Collins, Tanya (American Society for Nutrition, 2009)
Background: No studies have examined dietary patterns and breast cancer risk in a large cohort of African American women. Objective: We investigated the association between dietary patterns and breast cancer risk in the Black Women’s Health Study. Design: This is a prospective cohort study of 50,778 participants followed biennially from 1995 through 2007. During 443,742 person-years of follow-up, 1094 incident cases of breast cancer were identified. Factor analysis was used to derive food patterns based on 69 food variables. We used Cox regression models to obtain incident rate ratios (IRRs) for breast cancer in relation to quintiles of each of the 2 dietary patterns, with adjustment for other breast cancer risk factors. Results: Through factor analysis, we identified 2 dietary patterns: Western (refined grains, processed meat, and sweets) and prudent (whole grains, vegetables, fruit, and fish). The prudent diet was weakly associated with lower breast cancer risk overall; P for trend = 0.06. In analyses stratified by body mass index (BMI; in kg/m(2)), the prudent dietary pattern was associated with a significantly lower risk of breast cancer in women with a BMI <25 (IRR: 0.64; 95% CI: 0.43, 0.93; P for trend = 0.01). The prudent dietary pattern was also associated with a significantly lower risk of breast cancer in premenopausal women (IRR: 0.70; 95% CI: 0.52, 0.96; P for trend = 0.01), and we found a significant inverse association for the prudent dietary pattern and estrogen receptor–negative breast cancer (IRR: 0.52; 95% CI: 0.28, 0.94; P for trend <0.01). Conclusion: Our findings suggest that the prudent dietary pattern may protect against breast cancer in some black women.